2015
DOI: 10.1016/j.gore.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Primary debulking surgery for metastatic cervical adenocarcinoma: A case report

Abstract: HighlightsThe case presented is that of a primary debulking surgery for presumed ovarian cancer.Final pathology revealed diffusely metastatic endocervical adenocarcinoma.After primary chemotherapy, the patient has remained disease-free 30 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Angeles et al 34 have reported that surgery has a salvage role in patients with isolated recurrences after primary treatment with RT or CRT. Davenport et al 35 have reported that in cases with recurrent RT story, primary debulking should not be considered because of the advancements in chemotherapeutical field. On the other hand, Tseng et al 36 have reported that surgery could be an option in selected patient groups with stage IV CC with PC.…”
Section: Discussionmentioning
confidence: 99%
“…Angeles et al 34 have reported that surgery has a salvage role in patients with isolated recurrences after primary treatment with RT or CRT. Davenport et al 35 have reported that in cases with recurrent RT story, primary debulking should not be considered because of the advancements in chemotherapeutical field. On the other hand, Tseng et al 36 have reported that surgery could be an option in selected patient groups with stage IV CC with PC.…”
Section: Discussionmentioning
confidence: 99%